Recent development on key determinants of employees' innovative work behavior in knowledge intensive firms - Nur Farhana Zaidi; Nur Afifah Yakub; Tengku Adil Tengku Izhar (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
In order to remain competitive in an aggressive business environment, firms are embracing on innovation. Innovation is crucial for the process of identifying new opportunities and keeping the firm to be a few steps ahead of their competitors. Innovation of knowledge intensive firms is dependent to the knowledge workers and their innovative work behavior. In the literature review study, the author highlighted key determinants of employees' innovative work behavior in knowledge intensive firms in Malaysia which are transformation leadership, commitment (affective commitment, continuance commitment and normative commitment) and rewards (intrinsic reward and extrinsic reward). The literature review is significant to knowledge management scholars, policy makers and knowledge workers.
Keywords: 650; innovative work behavior; knowledge intensive firm; transformational leadership; commitment; reward